(untitled) (LEARNing Landscapes, 2011)
The article introduces the notion of a "meme." A meme is an idea, behavior, or style that spreads from person to person within a culture. In education it acts as a powerful assumption, guiding what is meant by learning and teaching and determines that teaching should include a textbook, teacher-directed lessons, control of student behavior, and testing as proof of "learning." The article explores new challenges to this meme coming from current research emerging out of biology, cognitive psychology, and neuroscience. It suggests that a form of project-based learning is more compatible with how the human brain was designed to make sense of experience.